ANALISIS AKUNTANSI KAS IMPEREST TERPUSAT PADA PT. PLN (Persero) UNIT INDUK PEMBANGUNAN XII - Amril Arifin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The purpose of this study to determine the application of imprest cash accounting system centered on PT PLN (Persero) Parent Unit Development XII, and to determine whether the cash imprest centralized accounting system implemented by PT PLN (Persero) Parent Unit XII can support the development of internal control of cash. The analytical method used in this research was to study the results of observations and data obtained from PT PLN (Persero) Parent Development Unit XII in order to understanding the conditions and problems arising from the old system. Then the evaluation of the internal control of cash. Imprest cash centralized accounting system implemented by PT PLN (Persero) Parent Unit XII Development has been fully supportive of management in conducting internal control of cash.